Respiratory Syncytial Virus Hospitalization During Pregnancy in 4 High-income Countries, 2010–2016. (24th May 2018) - Regan, Annette K; Klein, Nicola P; Langley, Gayle; Drews, Steven J; Buchan, Sarah; Ball, Sarah; Kwong, Jeffrey C; Naleway, Allison; Thompson, Mark; Wyant, Brandy E; Levy, Avram; Chung, Hannah; et al.
Abstract: Few studies have addressed respiratory syncytial virus (RSV) infection during pregnancy. Among 846 pregnant women hospitalized with respiratory illness and tested for RSV, 21 (2%) were RSV positive, of whom 8 (38%) were diagnosed with pneumonia. Despite study limitations, these data can help inform decisions about RSV prevention strategies.